Spine Tumor Epidemiology in Patients who Underwent Orthopaedic Surgery - N. S. Zaborovsky; D. A. Ptashnikov; E. E. Topuzov; E. V. Levchenko; D. A. Mikhailov; K. E. Natalenko (Travmatologiâ i Ortopediâ Rossii, 2019)
Purpose of the study — to evaluate the frequency of spine tumors in patients who underwent orthopaedic treatment in a specialized hospital.Materials and methods. Ап patients treated in the Vreden Russian Research Institute of Traumatology and orthopedics (rniito) with spine tumor diagnosis were examined from 2000 till 2017. The data was obtained from medical histories. Patients’ distribution per gender, age, histological type and tumor location was evaluated.Results. 2023 patients were included into the study, where 1298 (64.3%) were female. Patients with secondary metastases prevailed (59% overall), including breast cancer (43.6%), renal carcinoma (18%) and lung cancer (10.7%). Among benign tumors (overall 18.7%) symptomatic hemangiomas prevailed (93.8%). Primary malignant tumors (total 10.2%) were represented mainly by multiple myeloma (54.2%) and plasmacytoma (14.6%). Intermediate tumors with local aggressive growth were observed rarely (overall 3.9%).Conclusion. Spine is affected mainly by secondary tumors, where metastases of breast, renal and lung cancer are observed most often. Benign symptomatic hemangiomas demonstrate a high prevalence. Primary malignant tumors are presented mainly by multiple myeloma. Other primary malignant tumors and tumors with local aggressive growth are observed rather rarely.